The effects of prebiotic oligofructose on hematological, serum biochemical parameters and liver enzymes of juvenile beluga (Huso huso) - Hoseinifar, S.H.; Mirvaghefi, A.R.; Mojazi Amiri, B.; Khoshbavar Rostami, H.A.; Darvish Bastami, K. (2011)
The aim of the present study was to investigate the effects of dietary oligofructose (1, 2 and 3%) on blood profiles of beluga Huso huso juveniles (18.77±0.76g). After 7 weeks feeding on experimental diets hematological parameters, metabolic products (cholesterol, glucose and total protein) and serum enzymes (lactate dehydrogenase, alkaline phosphatase, alanine aminotransferase and aspartate aminotransferase) were measured. Compared to the control group (0% oligfructose), oligofructose had no effects on red blood cell counts (RBC), mean corposcular volume (MCV), mean cellular hemoglobin concentration (MCH) or mean cell hemoglobin concentration (MCHC) (P>0.05). However, hematocrit (Hct), hemoglobin concentration (Hb) and leucocyte counts (WBC) were significantly higher in fish fed 2% oligofructose (P<0.05). Although serum glucose and total protein remained unaffected, cholesterol was significantly lower in the 2% oligofructose group (P<0.05). Our results showed oligofructose had no significant effects on serum lactate dehydrogenase, alkaline phosphatase, alanine aminotransferase and aspartate aminotransferase (P>0.05). These results indicate an immunomodulatory effect and the potential to reduce serum cholesterol levels in beluga sturgeon. Published